Exploring Gender Differences within Forest Schools as a Physical Activity Intervention - Emilia Trapasso; Zoe Knowles; Lynne Boddy; Lisa Newson; Jo Sayers; Clare Austin (MDPI AG, 2018)
This study investigated whether children engaged in more physical activity (PA) on school days that included Forest School (FS) sessions than a regular school day or a school day with a Physical Education (PE) lesson. How FS sessions influenced children’s general levels of PA and wellbeing was also explored across gender. A mixed-methods study followed a sample of 59 child participants aged 7 to 9 years old, from four primary schools, whilst taking part in twelve weekly FS sessions. Measures included the PA Questionnaire for Older Children and accelerometry data together with an individual Write and Draw task to inform focus groups. Children had significantly greater levels of light PA on a FS day and a PE school day compared to a regular school day and children reported feeling both happier and relaxed as a consequence of the intervention. From the qualitative data, boys and girls reported different likes of the FS interventions, whereas their dislikes of FS were comparable. Findings from this research provide evidence for such outdoor, nature-based learning within the school curriculum contributing to daily PA in children.